Comparison of the Effectiveness of Hypnotherapy and Acceptance and Commitment Therapy on Chronic Fatigue Symptoms in Patients with Fibromyalgia in Tehran - Rasti , Leila; Maredpour, Alireza (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and hypnotherapy in reducing chronic fatigue symptoms among patients with fibromyalgia in Tehran.Methodology: The research employed a semi-experimental, randomized design with a pre-test, post-test, and three-month follow-up, including two intervention groups (ACT and hypnotherapy) and one control group. A total of 45 patients with fibromyalgia were selected through convenience sampling and randomly assigned to the three groups (15 per group). Participants in the intervention groups received eight sessions of ACT or ten sessions of hypnotherapy, respectively, while the control group received no psychological intervention and continued with standard pharmacological treatment. Chronic fatigue symptoms were assessed using the Jason Chronic Fatigue Syndrome Questionnaire at all three time points. Data analysis was conducted using multivariate analysis of covariance (MANCOVA), repeated measures ANOVA, and Bonferroni post-hoc tests via SPSS-26 software.Findings: The MANCOVA results revealed a significant difference in chronic fatigue symptoms between the three groups at both the post-test (F = 168.32, p < 0.001, η² = 0.88) and follow-up stages (F = 46.19, p < 0.001, η² = 0.79). Bonferroni post-hoc analysis showed that both ACT and hypnotherapy groups had significantly lower fatigue scores than the control group at post-test (p < 0.001), with no significant difference between ACT and hypnotherapy (p = 0.338). However, at follow-up, ACT remained significantly more effective than hypnotherapy (p < 0.001), indicating a more sustained impact.Conclusion: These findings highlight the importance of psychological therapies in managing complex somatic symptoms in chronic conditions.